SISTEM INFORMASI PENJUALAN CAT BERBASIS MULTIUSER: (Studi Kasus CV KARUNIA ABADI Semarang) - Elsiana Tri Andri Antini; Ahmad Ashifuddin Aqham (Pusat Riset dan Inovasi Nasional, 2024)
Growth of computer technology which is fast to progressively give amenities for human being in executing life activity, this matter result usage of computer is alternative taken by various institution because assessed more giving advantages compared to existing loss. Computer are appliance assist to improve performance various area. In finishing the problem of data processing in CV. Karunia Abadi, pursuant to execution of [done/conducted] survey, writer try to alter data-processing program by manual with computerization program.. This change aim gives freshment in the running of him. With computer program in data input still need time old ones and if for the seeking of data also still have to write one by one since it cannot by automatic and presentation which must be sent to leader still walk tardy so that cannot be presented anytime,because of this existence problem the writer try to formulate problems that is